Forest cover change in China from 2000 to 2016. Issue 2 (17th January 2022) - Guo, Jing; Gong, Peng; Dronova, Iryna; Zhu, Zhiliang
ABSTRACT: Due to favourable afforestation policies in the past few decades, China has become the nation with the greatest afforestation area in the world. However, there are few specific distribution maps of forest change at regional and national level in China. Here, we applied all available Landsat time series images in the growing seasons from 1990 to 2018 on the Google Earth Engine platform to track annual forest changes in China. Our validation indicates that the overall accuracy reached 89%. From 2000 to 2016, most forest change in China occurred on the east side of the Line of Huanyong Hu (a line linking Aihui in Northeast China and Tengchong in Southwest China dividing China into east and west parts). Forest growth is the major change type in China with a forest-area expansion of 494, 317 ± 22, 830 km 2 . Meanwhile, there have also been some forest losses mostly scattered in southern and northeastern China. The total loss of the forest area was 52, 856 ± 3366 km 2 . Thus, from 2000 to 2016, the net increase in forest area in China was 441, 461 ± 26, 196 km 2, which is approximately 4.6% of the terrestrial area of China, almost equivalent to the entire Thailand. Among these 16 years, there have also been some forest areas recovered or replanted after disturbances. Meanwhile, afforestation achievements and effectiveness have also met the great risk that some afforested areas are eventually destroyed back to previous non-forest land again. The areas for these two change types are 43, 728 ± 6574 km 2 and 18, 457 ± 2396 km 2, respectively. The results indicated great afforestation achievements, but there was also some loss of forest resources and threats to consolidating afforestation achievements in China. The results of this study offer greater detail of forest change, especially afforestation, and can provide useful information for forest management and ecological restoration evaluation. Additionally, the forest change result will be available online (https://doi.org/10.5281/zenodo.5501089 ).